Metodologia de projeto do conversor DAB aplicado a transformadores de estado sólido - Kirsten, André Luís (2014)
This thesis presents a design methodology for the dual active bridge converter, that includes the influence of the nominal phase-shift angle in the behavior of the DAB converter for entire power and voltage ranges. The analysis presented focus on two important performance parameters of the DAB converter: the nonactive power and the limits of ZVS operation. The study of these two parameters results in a prior knowledge of the qualitative characteristics of the conduction and switching losses, respectively. Using this knowledge it is possible to optimize the converter operation considering the priorities of application performance. The experimental results were performed for three different projects nominal angles and three different input voltages for the whole load range, and they prove the feasibility of the proposed analysis. The analyse of the limit ZVS area took into account the switches intrinsic capacitances, and the dead time between the complementary switches. The DAB converter placed at a three-stage structure applied to solid state transformer, has voltage ripple at low frequency in their bus voltages because of the connection into the distribution network. Thus, it becomes possible to apply a low frequency burst mode modulation, without needing to oversize the bus capacitors. Three burst mode modulations are evaluated in simulation. The modulation which performed better results in simulation was implemented in practice, and the experimental results showed significant improvement in the converter´s efficiency when it is operating in light loads. Finally, a discussion of the parameters to be evaluated for the DAB converter´s design is proposed.